Phylogenetic analysis and temporal diversification of the tribe Alsineae (Caryophyllaceae) with the description of three new genera, Hesperostellaria, Reniostellaria and Torreyostellaria - Xue, Bine; Song, Zhuqiu; Cai, Jie; Ma, Zhonghui; Huang, Jiuxiang; Li, Yuling; Yao, Gang (Frontiers in Plant Science, 2023)
Alsineae are one of the most taxonomically difficult tribes in Caryophyllaceae and consist of over 500 species distributed in the northern temperate zone. Recent phylogenetic results have improved our understanding on the evolutionary relationships among Alsineae members. Nevertheless, there are still some unresolved taxonomic and phylogenetic problems at the generic level, and the evolutionary history of major clades within the tribe was unexplored to date. In this study, we carried out phylogenetic analyses and divergence time estimation of Alsineae using the nuclear ribosomal internal transcribed spacer (nrITS) and four plastid regions (matK, rbcL, rps16, trnL-F). The present analyses yielded a robustly supported phylogenetic hypothesis of the tribe. Our results showed that the monophyletic Alsineae are strongly supported to be the sister of Arenarieae, and the inter-generic relationships within Alsineae were mostly resolved with strong support. Both molecular phylogenetic and morphological evidence supported the Asian species Stellaria bistylata and the two North American species Pseudostellaria jamesiana and Stellaria americana all should be recognized as new monotypic genera respectively, and three new genera Reniostellaria, Torreyostellaria, and Hesperostellaria were thereby proposed here. Additionally, molecular and morphological evidence also supported the proposal of the new combination Schizotechium delavayi. Nineteen genera were accepted within Alsineae and a key to these genera was provided. Molecular dating analysis suggested that Alsineae splitted from its sister tribe at ca. 50.2 million-years ago (Ma) during the early Eocene and began to diverge at ca. 37.9 Ma during the late Eocene, and divergent events within Alsineae occurred mainly since the late Oligocene. Results from the present study provide insights into the historical assembly of herbaceous flora in northern temperate regions.